Biological Markers in Diagnosis of ADHD: EEG Theta/Beta Ratio in Diagnosis of ADHD - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at the Research Institute Brainclinics, Nijmegen, Netherlands, conducted a meta-analysis on the Theta/Beta ratio (TBR) during Eyes Open from location Cz (the electrode halfway between the inion and the nasion) in the EEG of children/adolescents 6-18 years of age with and without ADHD.